Comments from the South - Cordero Velásquez, Tatiana (2011)
This text delves into the questions proposed by the Dossier ¿How is ‘queer’ thought of in Latin America? The author analyzes the issues of the political in the queer, its contributions and its limitations, and the relevance of the concept. Emphasizes the absence of a gender perspective in earlier gay and queer studies and the relation between LGBTI subjects and academy in the trajectory of the queer in our context. The text further analyzes the place of the feminine in three of the five articles that deal with gay and trans identities, and the absence of an analysis of the masculine in the lesbian, bisexual or trans masculine as a reflection of stratification in the production of knowledge about the queer body politic. At the same time, underlines the importance of this dossier in the production of knowledge in the South as well as the complexification of the debate.